Isoenzymatic variability in pear tissues for fingerprinting - Fachinello, José Carlos; Musacchi, Stefano; Zuccherelli, Silvia; Sansavini, Silviero (Pesquisa Agropecuaria Brasileira, 2000)
Eight self-rooted genotype of pear (Pyrus communis L.) were assessed to assert the patterns of the isoenzymatic systems b-glucosidase (E.C.3.2.1.21), esterase (E.C.3.1.1.2) and peroxidase (E.C.1.11.1.7). Tissues samples of buds, leaves, shoot bark and in vitro leaves were analyzed by polyacrylamide gel electrophoresis (5% to 12.5%). High variability of esterase isoenzyme was detected among the tissues of each cultivar. The b-glucosidase activity was detected only in in vitro leaves, otherwise polymorphism was not found. High variability of peroxidase in all pear genotypes was found with isoenzyme extract from buds. The other tissues showed enough variability, although less variability was detected for differentiation of all assayed cultivars. Esterase proved to be most reliable enzyme for identification of pear cultivars and in the other two were less effective in all the tissues tested.